Adoecimento psíquico de pastores evangélicos das Assembléias de Deus do Brasil ligadas à CGADB – (Convenção Geral das Assembléias de Deus do Brasil) - Goulart, Valquíria Andréia Salinas (2023)
Introduction: The prevalence of emotional disorders – depression, anxiety – is often reported in the Ministries of Evangelical Pastors. However, little attention has been paid to this subject. Objective: The scope of the study was to investigate the predominance of depression and anxiety in the emotional health of evangelical pastors of the Assembly of God of Brazil linked to CGADB. Specific objectives: In addition, to understanding the factors associated with emotional disorders, pointed out by the research, the investigation correlated the indices of mental disorders with quality of life and proposed an action in order to promote awareness of the importance of the emotional health of the religious. The study took part in 163 evangelical pastors from national and international scopes, all men and Brazilians aged 25 years up and working in the Ministry of the Assembly of God church of Brazil. Material and methods: exploratory cross-sectional study, in which an online questionnaire with twenty-seven questions was used, created by the researcher herself and some validated indexes, Depression Beck Scales and Sf36. Results: the research has the exploratory nature and, being a survey by sampling, demonstrated the existence of a considerable number of pastors suffering from hopelessness, anxiety, and depression, requiring help from a professional. Conclusion: it was observed in this exploratory sampling, where 54.6 % of those who responded live in the southeast, and have 40 to 55 years, as well as 1 to 10 years of ministry, the research reveals that there is a trait of depression and minimal anxiety (which do not characterize disease). Regarding the effective presence of depression, ranging from mild to severe, the prevalence was 8.0% in our sample. The presence of anxiety, between mild and severe, was found 18.4%. Therefore, it concludes with these data that there is a significant presence of hopelessness among them